The Lerner Index and Firm Profitability: Empirical Evidence from the Sweet Potato Industry in Kenya - Odondo, Alphonce (EuroEconomica, 2025)
This study examines how the market power of sweet potato wholesalers in Kenya influences their profitability, using the Lerner Index as the main measure. Drawing on cross-sectional data from 50 wholesalers in Homa Bay County, the research applies both linear and nonlinear regression models to assess how pricing freedom, cost efficiency, firm size, product differentiation, and overall market structure shape gross profit margins. The linear results suggest that wholesalers who can exercise more control over their prices generally earn higher profits. However, the nonlinear model provides a more nuanced insight: profitability rises with market power only up to a certain point, after which it begins to fall. This inverted U-shaped pattern indicates that while moderate market power is beneficial, too much dominance may create inefficiencies that ultimately reduce returns. The study also finds that cost efficiency and larger firm size meaningfully enhance profitability, whereas market concentration and product differentiation do not show direct independent effects. With strong R² values of 0.77 and 0.80 and no signs of autocorrelation, both models are statistically reliable. The study recommends fostering a competitive environment that still allows reasonable pricing flexibility, while emphasizing improvements in cost management, logistics, storage, and transport to boost wholesalers’ financial performance.